Une Dissection Coronaire Spontanée Récidivante - M Touré; A Bilonda; HO Ba; AA Diall; VH Nguyen; I Menta (HEALTH SCIENCES AND DISEASE, 2022)
RESUME La dissection coronaire spontanée est une cause fréquente de syndrome coronaire aigu ou de mort subite chez la femme, en particulier la femme jeune sans ou avec peu facteurs de risque d’athérosclérose. Son diagnostic repose sur l’angiographie coronaire parfois couplée à l’imagerie endocoronaire en occurrence la tomographie par cohérence optique. Sa prise en charge thérapeutique est basée sur le traitement conservateur avec une évolution favorable et un bon pronostic dans la grande majorité des cas. ABSTRACT Spontaneous coronary dissection is a common cause of acute coronary syndrome or sudden death in women, especially young women with little or no risk factors for atherosclerosis. Its diagnosis is based on coronary angiography, sometimes coupled with endocoronary imaging, in this case optical coherence tomography. Its therapeutic management is based on conservative treatment with a favorable course and a good prognosis in the vast majority of cases. However, there is currently no sufficient means to prevent recurrences apart from a few commonsense measures such as optimal control of blood pressure or contraception in women of childbearing age.